AA147 ameliorates post-cardiac arrest cerebral ischemia/reperfusion injury through the co-regulation of the ATF6 and Nrf2 signaling pathways - Yuan, Zhu; Lu, Liping; Lian, Yingtao; Zhao, Yuanrui; Tang, Tingting; Xu, Song; Yao, Zhun; Yu, Zhui (Frontiers in Pharmacology, 2022)
Ischemia/reperfusion caused by cardiac arrest (CA) disturbs endoplasmic reticulum (ER) homeostasis and redox balance in neurons. AA147, originally developed as a pharmacologic activator of the activating transcription factor 6 (ATF6), can protect multiple tissues from ischemia/reperfusion injury (IRI) by decreasing reactive oxygen species (ROS) and restoring ER function. However, it is unclear whether pharmacologic treatment of AA147 could ameliorate post-CA cerebral IRI and whether it is associated with proteostasis regulation and anti-oxidative stress mechanism. In the present study, mice were subjected to 9 min-CA surgery followed by cardiopulmonary resuscitation (CPR). AA147 or vehicle was administered 1 day before the operation and 15 min after the return of spontaneous circulation. We found that AA147 restored neurological function and reduced dead neurons in mice suffering from CA. Moreover, AA147 inhibited CA/CPR-caused neuronal apoptosis and ER stress, indicated by reduced TUNEL-positive neurons, surged expression of Bcl-2/Bax, and down expression of cleaved caspase-3, caspase-12, C/EBP homologous protein (CHOP). The expression of ATF6 and its regulated gene glucose-regulated protein 78 (GRP78) increased significantly after the administration of AA147, suggesting the activation of the ATF6 pathway. In addition, AA147 also alleviated the upsurge of the ROS generation and MDA levels as well as increased SOD activity, accompanied by enhancement of the nuclear factor E2-related factor 2 (Nrf2) and its modulated heme-oxygenase-1 (HO-1) expressions. Cotreatment of AA147 with inhibitors of the ATF6 or Nrf2 significantly suppressed AA147-dependent reductions in ROS scavenging and neuronal death after CA/CPR. The results suggested that AA147 could confer neuroprotection against post-CA cerebral IRI through inhibition of oxidative stress along with ER stress-associated apoptosis, which is attributed to the coregulation of both ATF6 and Nrf2 signaling pathways activity. Our findings support the potential for AA147 as a therapeutic approach to improve post-CA brain injury.